The Role of Business Contracts in Minimizing the Risks of Corporate Cooperation - Mulyani Santoso (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Intercompany collaboration is an integral strategy in the dynamics of the modern business world, but it carries with it various potential risks that can lead to losses and disputes. In this context, business contracts play a crucial role not only as a basis for agreements but also as a legal instrument for managing and minimizing collaboration risks. This study aims to analyze the role of business contracts as a risk allocation mechanism and examine the factors that contribute to their ineffectiveness in minimizing risk in practice. This research uses a normative legal method with a statutory and conceptual approach. The legal materials used consist of primary legal materials in the form of laws and regulations, as well as secondary legal materials in the form of books and journals relevant to contract law. The analysis was conducted qualitatively with a descriptive-analytical approach. The research results show that, theoretically, business contracts function as risk allocation instruments capable of identifying, distributing, and controlling risks in corporate collaborations. However, in practice, contracts often fail to perform this function optimally because they are drafted without adequate risk analysis, use standardized templates, and lack operational clauses. Therefore, a risk-based contract development approach is needed, emphasizing risk identification, allocation of responsibilities, and the formulation of clear and applicable clauses. Thus, a properly drafted business contract not only provides legal certainty, but also serves as an instrument for preventing disputes and protecting the interests of the parties in corporate cooperation. Keywords : business contracts, risk mitigation, corporate cooperation, risk allocation